Alpha, Beta- Unsaturated Lactone-Nitrone Cycloadditions: a Route to the Synthesis of (±)–Tussilagin - Mohammed A. Al-Nuri (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Reaction of nitrone (V with a, f1 -unsaturated lactone C.4) resulted in the isolation of a single adduct (7). The observed high regiochemical control has encouraged further explorations of natural product synthesis. A route to the synthesis of an interesting member of Pyrrolizidine- Alkaloid family; (±) -Tussilagin 90/ has been described.